EFFECTS OF BOLUS DOSE AND CONTINUOUS INFUSION OF TRANEXAMIC ACID ON BLOOD LOSS AFTER CORONARY ARTERY BYPASS GRAFTING - Ahmad, Imtiaz; Islam, Mujahid -ul-; Islam, Ansa; Shah, Azmat Ali (Journal of Ayub Medical College Abbottabad, 2014)
Background: Cardiac surgery is associated with excessive bleeding that is as a result of coagulopathy caused by cardiopulmonary bypass. We evaluated the effect of two different modalities for administering similar doses of tranexamic acid on bleeding following primary elective coronary artery bypass grafting (CABG). Methods: In the randomized control trial. 137 patients scheduled for CABG were randomized to two groups applying different modalities of tranexamic acid administration (bolus injection of 30 mg/kg vs. continuous infusion). Blood loss until removal of chest tubes was the primary outcome measure; we also recorded and assessed blood products transfused, and length of ICU stay. Results: Both the groups were comparable at baseline. Trends toward transfusion differences between groups were not statistically significant. No differences in length of ICU stay, morbidity or mortality were found. Conclusion: In CABG surgery, the use of either method for administering similar doses of tranexamic acid leads to a similarl reduction in postoperative mediastinal bleeding. Keywords: Tranexamic acid, CABG, cardiac surgery, antifibrinolytic